2024
DOI: 10.1111/fare.12990
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the field. Toward evidence‐based parenting support to promote positive parenting in children's sport

Matthew R. Sanders,
Cassandra K. Dittman,
Clifford J. Mallett
et al.

Abstract: ObjectiveThe development of a brief online program to improve prosocial parent behavior at children's sporting events is described. We provide an overview of the collaborative research and development process, the theoretical basis for program content, design features, and evaluation approach used to establish the feasibility of Play Well Triple P in Junior Rugby League.BackgroundParents influence children's experience of sports, impacting their enjoyment and participation, motivation to play, behavior, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Clearly, targeted and bespoke programs are needed that support parents to engage in behaviours that facilitate positive involvement in their children's sport (Sanders et al 2024). A vast body of evidence has shown that parenting programs that teach parents to engage in positive and constructive parenting practices has a positive impact on children's mental health and development (Barlow and Coren 2018;Jewell et al 2022), with a handful of studies demonstrating the feasibility and efficacy of doing this in a junior sports context (e.g., Dowell et al 2021;Smoll et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, targeted and bespoke programs are needed that support parents to engage in behaviours that facilitate positive involvement in their children's sport (Sanders et al 2024). A vast body of evidence has shown that parenting programs that teach parents to engage in positive and constructive parenting practices has a positive impact on children's mental health and development (Barlow and Coren 2018;Jewell et al 2022), with a handful of studies demonstrating the feasibility and efficacy of doing this in a junior sports context (e.g., Dowell et al 2021;Smoll et al 2007).…”
Section: Introductionmentioning
confidence: 99%